2004
DOI: 10.1590/s0073-47212004000400012
|View full text |Cite
|
Sign up to set email alerts
|

The influence of shell species and size on the shell selection pattern of Paguristes tortugae (Decapoda, Diogenidae) from Anchieta Island (Ubatuba, Brazil)

Abstract: ABSTRACT. Shell selection by the hermit crab Paguristes tortugae Schmitt, 1933 from Anchieta Island (Brazil) was analyzed using the six most frequently occupied shell species in the field and taking into account the sexual condition of the individuals, the shell size and the shell species. The experiments were conducted under laboratory conditions and the shell species preference was estimated on the basis of the frequency that each species was chosen by the individuals. The preferred shell species and size we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…Nos estudos realizados no litoral de São Paulo, Calcinus tibicen apresentou melhores correlações entre o tamanho e o peso dos ermitões com o peso da concha (MANTELATTO & GARCIA, 2000), Paguristes tortugae Schmitt, 1933 entre o peso do animal e o peso e o volume interno das conchas (DOMINCIANO & MANTELATTO, 2004); no estudo com L. loxochelis, as melhores relações foram entre o comprimento do própodo quelar esquerdo e o comprimento da abertura da concha (MARTINELLI & MANTELATTO, 1999).…”
Section: Discussionunclassified
“…Nos estudos realizados no litoral de São Paulo, Calcinus tibicen apresentou melhores correlações entre o tamanho e o peso dos ermitões com o peso da concha (MANTELATTO & GARCIA, 2000), Paguristes tortugae Schmitt, 1933 entre o peso do animal e o peso e o volume interno das conchas (DOMINCIANO & MANTELATTO, 2004); no estudo com L. loxochelis, as melhores relações foram entre o comprimento do própodo quelar esquerdo e o comprimento da abertura da concha (MARTINELLI & MANTELATTO, 1999).…”
Section: Discussionunclassified
“…Secondly, the occupation of a specific shell is influenced either by the interactions among hermit crabs, such as intra-specific competition for the shell, or by other resources (Bertness 1980, Gherardi and Nardone 1997, Dominciano and Mantelatto 2004, Sant'Anna et al 2006b), coexistence of different hermit crabs species (Kellog 1977, Bertness 1980, Gherardi and Nardone 834 SARA R. SAMPAIO and SETUKO MASUNARI 1997, Floeter et al 2000, Turra 2003, Sant'Anna et al 2006b), predation (Bertness 1982, Rotjan et al 2004), presence of gastropods in the community (Bertness 1980, Turra and Leite 2001, Sant'Anna et al 2006a, previous experience (Hazlett 1993, Hahn 1998, Meireles et al 2008, Alcaraz and Kruesi 2009) and formation of aggregations (Hazlett 1981, Turra andLeite 2000a). The hermit crab ability in detecting odours of died or dying gastropods was also reported (Kratt andRittschof 1991, Chiussi et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Among these characteristics are weight (Hahn 1998, Dominciano and Mantelatto 2004, Turra and Leite 2004, size (Bertini andFransozo 2000, Turra andLeite 2004), opening size (Botelho and Costa 2000, Bertini and Fransozo 2000, Sant'Anna et al 2006a) and architecture and volume (Gherardi and Nardone 1997, Floeter et al 2000, Shih and Mok 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted by Abrams (1978), Elwood et al (1979), Siu and Lee (1992), Ohmori et al (1995), Hahn (1998), Dominciano and Mantelatto (2004), found that the hermit crabs in the laboratory preferred those shell species most occupied in the field. A similar pattern of shell selection also was found in the present study.…”
Section: Shell-species Preferencementioning
confidence: 81%